The effectiveness of gamification in teaching vocabulary to young learners - Cortez Erraez, Viviana Abigail; Macas Quizhpe, Sara Cecilia; Recalde García , Frans Andrés (Arandu UTIC, 2025)
Students often forget new vocabulary words, highlighting the importance of exploring strategies such as gamification to enhance vocabulary acquisition in young English as a Second Language (ESL) learners. The rapid integration of digital tools and playful learning environments has positioned gamification as a promising method to increase student motivation and engagement. This article, based on a literature review, analyzes the use of game elements such as points, badges, and leaderboards, and their potential to improve vocabulary retention and understanding in young learners.The findings from the reviewed studies indicate that gamification significantly enhances vocabulary retention and encourages active participation. Additionally, key factors such as the level of challenge and social interaction are identified as influencing its effectiveness. These results suggest that integrating gamification into vocabulary teaching can be a valuable tool to support language development, strengthening intrinsic motivation and promoting a deeper commitment to learning. This article provides a basis that supports the use of gamified strategies in the classroom, encouraging educators to adopt innovative approaches in vocabulary teaching.